Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1002/ajp.22550
|View full text |Cite
|
Sign up to set email alerts
|

The importance of protein in leaf selection of folivorous primates

Abstract: Protein limitation has been considered a key factor in hypotheses on the evolution of life history and animal communities, suggesting that animals should prioritize protein in their food choice. This contrasts with the limited support that food selection studies have provided for such a priority in nonhuman primates, particularly for folivores. Here, we suggest that this discrepancy can be resolved if folivores only need to select for high protein leaves when average protein concentration in the habitat is low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 98 publications
(116 reference statements)
2
53
1
Order By: Relevance
“…, Ganzhorn et al. ). For example, if studies are limited to measures of crude or total energy, it is possible to overlook the different roles that the different energy‐providing constituents may have, as well as potentially conflicting interactions with other nutritional constituents.…”
Section: Resultsmentioning
confidence: 99%
“…, Ganzhorn et al. ). For example, if studies are limited to measures of crude or total energy, it is possible to overlook the different roles that the different energy‐providing constituents may have, as well as potentially conflicting interactions with other nutritional constituents.…”
Section: Resultsmentioning
confidence: 99%
“…The two artiodactyl species-cattle (herbivorous foregut fermenters) and bush pigs (omnivores with simple gut morphology)-harbored the most diverse microbiota (Kruskal-Wallis, FDR-adjusted P < 0.001; Fig. S3), whereas the three lemur species, two of which are hindgut fermenters [61,62], exhibited moderate microbial diversity (Fig. S3).…”
Section: Microbiome Compositionmentioning
confidence: 99%
“…Similarly, we also found that ADF and ADL of food items consumed by captive R. strykeri did not differ significantly from nonconsumed food items. Taken together, these data suggest that the protein concentration of foliage rather than the fiber concentration may be a nutritional priority for R. strykeri , and that protein and fiber selection for many primate species may represent two separate goals or processes (Ganzhorn et al, 2017).…”
Section: Discussionmentioning
confidence: 92%